Quality of consolidation of sandy-clay agglutinant sands by pneumatic stream with further compressing - D. M. Kukuj; D. M. Golub (Литьë и металлургия, 2003)
The receives results of investigations at NP RUP ''Institute BelNIILIT' showed that there exists the real possibility of using of the developed technology of the agglutinant sand compacting with further pressing at the works.